Disappearing rooms: the hidden theaters of immigration law - Castañeda, Michelle (Dissident acts, 2023)
In Disappearing Rooms Michelle Castañeda lays bare the criminalization of race enacted every day in US immigration courts and detention centers. She uses a performance studies perspective to show how the theatrical concept of mise-en-scène offers new insights about immigration law and the absurdist dynamics of carceral space. Castañeda draws upon her experiences in immigration trials as an interpreter and courtroom companion to analyze the scenography - lighting, staging, framing, gesture, speech, and choreography - of specific rooms within the immigration enforcement system. Castañeda’s ethnographies of proceedings in a “removal” office in New York City, a detention center courtroom in Texas, and an asylum office in the Northeast reveal the depersonalizing violence enacted in immigration law through its embodied, ritualistic, and affective components. She shows how the creative practices of detained and disappeared people living under acute duress imagine the abolition of detention and borders. Featuring original illustrations by artist-journalist Molly Crabapple, Disappearing Rooms shines a light into otherwise hidden spaces of law within the contemporary deportation regime. Duke University of Press Scholars of Color First Book Award Recipient